85 éves az egyetem főépülete - Béres, Zsuzsa (Gerundium, 2017)
The 85-Year-Old Main Building of the University. What is today the main building of the University was inaugurated on May 15, 1932. Construction work on the monumental edifice took four years and on completion it was capable of accommodating, after 20 years of waiting, three faculties of the institution, as well as the various university offices. In a retrospective survey, the discussion highlights the most significant moments of the emergence of the main building from the laying of the cornerstone to its inauguration.